Web-based model for enhancing communication in construction - Indayani Sularso (2008)
This dissertation is motivated with the aim of developing a web-based model to cope with the communication problems for large and complex project to overcome time and the organization boundaries between the owner and the construction manager. This web-based model will facilitate electronic project report by taking full advantage of the common office software (i.e. MS Excel 2000, MS Access 2000, and MS FrontPage 2000) and without sophisticated IT requirement. It offers a number of benefits such as easier access to necessary information, timely information and data transfer, quality reporting, and time saving. Furthermore, the decision making process could be improved contributing to a better project performance. However, the improvement in providing more timely information could not be achieved if this web-based model is used only to support what is currently being done. Some changes in the current work procedure or work schedule should also be done. Eventually, by improving the availability, accessibility, timeliness, and interactivity of the project report, the communication between project participants is enhanced and gives a contribution to project performance improvement.